Link2Practice: A Model of Ongoing Teacher and Teacher Candidate Professional Learning - Sanford, Kathy; Robertson, Kerry; Hopper, Timothy; Collyer, Vivian; Lancaster, Laura (Alberta Journal of Educational Research, 2020)
A common complaint about teacher education programs is that it follows a linear model—where theory and teaching skills are learned at the university and then applied in practicum experiences—that is inadequate and does not accurately represent teacher candidates’(TC) experiences (Brouwer & Korthagen, 2005; Korthagen, Loughran & Russell, 2006). Indeed, teacher education programs have long been faced with the challenge of a “theory/practice divide”, creating what has been seen as a mechanistic separation between university programs (where it is implied theory is learned) and the practicum (where it is implied skills and strategies are learned). This divide continues once teacher candidates become teachers in their own classrooms, where the divide further widens by valuing of the practical over the theoretical. We need a new frame of reference to understand teacher education as a whole (throughout a professional career), as emerging from interconnected, non-linear, and at times unpredictable structures. Teacher education programs should form in relation to teacher professional learning, student learning, and the realities of dynamically evolving modern-day schools. In our institutions, the ongoing tension between learning sites of campus and schools is reduced in the teacher education partnership called Link2Practice, where TCs’ courses are integrated in a school district program with teachers who are making inquiries into their practice. This partnership responds to the increasing need for educators to understand and remain current about the interactions between TCs, K-12 public schools’ students and the pedagogy practices, informed by theory, that they advocate. This paper describes the development of the Link2Practice model and discusses its importance for teacher education. Keywords: Teacher education; partnerships; integration; professional learning On reproche souvent aux programmes de formation des enseignants de suivre un modèle linéaire—selon lequel la théorie et les compétences pédagogiques sont acquises à l’université pour ensuite être appliquées pendant les stages—qui est inadéquat et qui ne représente pas avec exactitude les expériences des stagiaires (Brouwer & Korthagen, 2005; Korthagen, Loughran & Russell, 2006). En effet, les programmes de formation des enseignants font face depuis longtemps au défi que représente l’écart entre la théorie et la pratique ayant créé ce qu’on perçoit comme étant une séparation mécaniste entre les programmes universitaires (où il est sous-entendu que les étudiants apprennent la théorie) et les stages (où il est sous-entendu que les étudiants apprennent des habiletés et des stratégies). Cet écart se poursuit quand les stagiaires commencent à enseigner dans leur propre salle de classe et se creuse par la valorisation de la pratique aux dépens de la théorie. Il nous faut un nouveau cadre de référence qui permettra de comprendre la formation des enseignants dans son ensemble (tout au long de la carrière d’enseignant) comme produit de structures interconnectées, non linéaires et parfois imprévisibles. Les programmes de formation des enseignants devraient exister en relation avec le perfectionnement professionnel des enseignants, l’apprentissage des élèves et les réalités des écoles modernes en évolution dynamique. Dans nos institutions, la tension constante entre les deux sites d’apprentissage—le campus et les écoles—est réduit grâce à un partenariat éducatif nommé Link2Practice par lequel les stagiaires sont intégrés dans un programme de district scolaire avec des enseignants qui font enquête sur leur pratique. Ce partenariat répond au besoin croissant qu’ont les enseignants de comprendre les interactions entre les stagiaires, les élèves M-12 des écoles publiques et les pratiques pédagogiques informées par la théorie qu’ils préconisent, et de rester au courant de ces interactions. Cet article décrit le développement du modèle Link2Practice et discute de son importance dans la formation des enseignants. Mots clés : formation des enseignants; partenariats; intégration; perfectionnement professionnel